2021
DOI: 10.3390/ijerph18073470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on the Oral Microbiota and Saliva of Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Exercise can be hypothesized to play an important role in non-alcoholic fatty liver disease (NAFLD) treatment by changing the oral bacterial flora and in the mechanism underlying periodontal disease. We performed salivary component analysis before and after an exercise regimen, and genome analysis of the oral bacterial flora to elucidate the underlying mechanism. Obese middle-aged men with NAFLD and periodontal disease were allocated to 12-week exercise (n = 49) or dietary restriction (n = 21) groups. We colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Moreover, these practices have the potential to improve treatment-related dysbiosis in other parts of the alimentary canal: the oral cavity, for example. 129 135 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these practices have the potential to improve treatment-related dysbiosis in other parts of the alimentary canal: the oral cavity, for example. 129 135 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these practices have the potential to improve treatment-related dysbiosis in other parts of the alimentary canal: the oral cavity, for example. [129][130][131][132][133][134][135] There is the potential that treatment-induced microbial biosis could eventually be avoided altogether. Many emerging cancer therapeutics promise targeted mechanisms and a reduction in adverse effects, which may eventually include perturbations to gut flora.…”
Section: Synbiotic Supplementsmentioning
confidence: 99%
“…Two studies performed in healthy adults that underwent a 12-week aerobic PA intervention (3 sessions of 30 min per week) or 7-week high-intensity interval training (consisting of swimming lengths) reported an increase in microbial alpha-diversity 111,119 weeks; 3 sessions of 90 min per week), but no significant changes in alpha-diversity were detected after the intervention 96 . Most of the studies in unhealthy individuals did not report any significant changes in alpha-diversity after a PA intervention 94,95,122,124,125,102,[106][107][108]114,115,118,121 . However, the chronic effect of PA on microbiome composition becomes clearer in the beta-diversity analysis, where more studies agree on a significant dissimilarity in the microbial communities of the individuals after long-term PA 94,95,[118][119][120]123,125,98,101,102,108,111,112,114,115 that were classified as responders compared to non-responders 122 .…”
Section: Chronic Effects Of Pamentioning
confidence: 99%
“…Most of the studies in unhealthy individuals did not report any significant changes in alpha-diversity after a PA intervention 94,95,122,124,125,102,[106][107][108]114,115,118,121 . However, the chronic effect of PA on microbiome composition becomes clearer in the beta-diversity analysis, where more studies agree on a significant dissimilarity in the microbial communities of the individuals after long-term PA 94,95,[118][119][120]123,125,98,101,102,108,111,112,114,115 that were classified as responders compared to non-responders 122 . Later studies have also reported an increase in A. muciniphila in participants with overweight/obesity or type 2 diabetes after long-term PA 101,114 .…”
Section: Chronic Effects Of Pamentioning
confidence: 99%
See 1 more Smart Citation